Pengaruh Kompensasi dan Beban Kerja Terhadap Kinerja Karyawan Pada Perusahaan Perhimpunan Penghuni Menara Karya - Luthfi, Venissa Keizia; Jakfar, Jakfar (Peneliti.net, 2024)
The Influence of Compensation and Work Load on Work Employee Performance at The Karya Tower Residents Association Company, Management Study Program, Faculty of Economics and Business, Jayabaya University, under the guidance of Dr. Jakfar SE., MM. The purpose of this study was to analyze and determine the effect of compensation and workload on employee performance at the Karya Tower Residents Association Company. The population in this study were employees of the Karya Tower Residents Association Company totaling 41 employees. Because the population is not more than 100 people, this study uses a census technique or saturated sample where the entire population is taken as a sample. Data collection in this study used quantitative data processed with SPSS. As for the data analysis techniques used in this study are multiple linear regression, partial test (t test), simultaneous significance test (F test), and the coefficient of determination. The result showed that the compensation variable had significant and positive effect on employee performance with the t test results, namely of 5.894 > 2.023 with a significance of 0.000 < 0.005. The workload variable has no significant and negative effect on employee performance with the t test results, namely of 1,592 < 2,023 with a significance of 0.120 > 0.005. Test conducted simultaneously show that compensation and workload have a significant dan positive effect on employee performance of the Karya Tower Residents Association Company with the results of the F test, namely of 18,587 > 3.245 with a significance value of 0.000. The R Square value is 0.495 or 49.5%, which means that there is an effect of compensation and workload on employee performance of 49.5%, while the remaining 50.5% is influenced by other variables or factors not included in this study.